Histomorphomertric Analysis Of Hormonal Contraceptive Pills On Anterior Pituitary Gland In Female Wister Rats - A Abubakar S.; Ladan B.A Yakubu A.A (Journal of Endocrinology and Hormones, 2023)
Millions of women use hormonal contraceptive pills around the world and though the physical effects are thoroughly described in the literature and clinical setting. The psychological effects have been largely ignored until recently. Recent studies have found that the use of hormonal contraceptives has an effect on women’s hormones and psychological well-being. The aim of this present research was to check the effect of hormonal contraceptive pills on anterior pituitary gland among female wister rat histomorphometrically. Thirty (30) female wister rats of 3 month old weighing 150 – 200g were used for the study. They were divided into three (3) groups of 10 rats each. Group one (1) received Microlut Levonorgestrel 30mg at a dose of 0.18g/kg while group two (2) received a combination of microgynon levonorgesrel 150mg and ehinylestadiol 130mg at a dose of o.18g/kg in 5 days cycle while group three (3) serve as control group. The experiment last for 72 days. Histomorphometrical analysis of anterior pituitary gland was carried out. The findings revealed that combined oral contraceptive pills adversely cause the decrease in the cells of the anterior pituitary more than the progestin only pills.
Keywords: Oral contraceptive pills